Software Integrated Personalized Biosensing Device for Serum Creatinine Detection Based on Boron doped MXene Nanohybrid - Divya N.; Nandi I.; Mendki N.; Chandra P. (My University, 2025)
In recent years, an increase in the number of chronic kidney disease (CKD) cases has led to a global health burden majorly affecting underdeveloped and developing nations. A key biomarker for assessing the kidneys’ normal functioning is creatinine, which is filtered out from the blood by the kidney. Thus, timely and specific detection of creatinine becomes necessary for diagnosis and subsequent treatment of CKD. Hence, in this study, we have tried to develop a field-deployable, software-integrated immunosensor for the detection of creatinine in a serum sample. The immunosensor was developed by incorporating gold nanoparticles, boron doped MXene, polyaniline, and anticreatinine antibody using an appropriate bioconjugation reaction. The developed sensor was able to detect creatinine in a linear dynamic range of 10 nM to 0.1 M with a limit of detection of 1.72 (±0.07) nM. The sensor was integrated with an indigenously developed software named “CretCheck” which simplifies the process of data analysis. The software integrated personalized biosensing device was used to find the creatinine concentrations directly from the obtained analytical signals. The developed immunosensor with the integrated software can also be implemented directly in primary health care facilities for creatinine detection in the future. © 2024 American Chemical Society.